Manajemen Program Teaching Factory Berbasis Link and Match di SMK TI Global Jimbaran - Santhi Dewi, Komang Hari; Novita, Ni Kadek Tasya; Jayanti, Ni Wayan Sri; Sudiatmika, I Putu Gede Abdi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the effectiveness of the Teaching Factory (TeFa) program management based on the link and match principle at SMK TI Global Jimbaran in enhancing students’ job readiness and entrepreneurial mindset. The research adopts a mixed-methods approach with a sequential explanatory design, starting with quantitative data collection through questionnaires distributed to50 students from grades XI and XII, as well as 10 vocational teachers and industry partners. Subsequently, in-depth interviews and observations were conducted to enrich the findings qualitatively. Quantitative analysis reveals that 82.7% of students stated that the TeFa program improved their understanding of industrial work processes, while 76% expressed interest in developing their own business after participating in TeFa activities. Furthermore, 90% of teacher respondents reported that the Teaching Factory supports contextual implementation of the Merdeka Curriculum. The qualitative analysis reinforces these findings by identifying active collaborative practices between the school and industry stakeholders, including the development of teaching modules, use of industrial-standard equipment, and student internships at partner companies. Based on these results, it is concluded that the management of the Teaching Factory at SMK TI Global Jimbaran has proven effective in implementing the link and match principles and in strengthening students’ entrepreneurial capacities..